Đào Duy Anh (1904-1988). Le parcours semé d’embûches d’un historien - Phan Huy Lê (Moussons, 2014)
Beyond a discreet and moving tribute to Đào Duy Anh, “master loved and respected”, who so deeply marked successive generations of Vietnamese intellectuals, the author traces, with precision and rigor, the social, intellectual, and scientific path of one of the most important historians lexicologists and Vietnam contemporary.